Effect of TeO2 addition on the gamma radiation shielding competence and mechanical properties of boro-tellurite glass: an experimental approach - M.I. Sayyed; Nidal Dwaikat; M.H.A. Mhareb; Ashwitha Nancy D'Souza; Nouf Almousa; Y.S.M. Alajerami; Fahad Almasoud; K.A. Naseer; Sudha D. Kamath; Mayeen Uddin Khandaker; Hamid Osman; Sultan Alamri (Journal of Materials Research and Technology, 2022)
We experimentally investigated the effect of TeO2 on the radiation-shielding competence of a BaO–MoO3–B2O3 glass system. Two gamma-ray sources (137Cs and 166Ho) and a scintillator detector (sodium iodide (NaI(Tl)) were utilized to measure the attenuation factors of the prepared glass at 0.184, 0.280, 0.662, 0.710, and 0.810 MeV. The measured mass attenuation coefficient agreed well with the theoretically calculated values for all the prepared samples. The linear attenuation coefficient (LAC) results demonstrated that as the photon energy increased, the penetrating ability of the photons through the glass increased. The LAC values of boro-tellurite glass at 662 keV were compared with those of other tellurite glass. We found that MTB1 glass produced better attenuation results than 10Li2O–20K2O–50B2O3–20TeO2 glass, whereas MTB5 glass with 70 mol% TeO2 had an LAC value greater than that of 90.4TeO2-9.6ZnO–4NiO glass. The half-value layer (HVL) increased continuously with photon energy. For MTB1 glass, the HVL increased from 0.3609 cm at 184 keV to 1.6078 cm at 662 keV and 1.8381 cm at 810 keV. The lowest set of HVL values was observed for MTB5 glass, which confirmed its superior attenuation properties compared to other compositions. The transmission factor (TF) was also calculated; MTB5 glass had the lowest TF values, which revealed that MTB5 provided the best shield. For glass with a thickness of 1 cm, the TF was 75.8% for MTB1, 72.8% for MTB2, 70.6% for MTB3, 68.8% for MTB4, and 63.4% for MTB5.